1991
DOI: 10.1111/j.1151-2916.1991.tb04304.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Alumina Ceramics in Caustic Alkaline Solutions at High Temperatures

Abstract: The corrosion rate and changes in the microstructure and fracture strength of alumina ceramics (93.0% A1203 and 99.5% A I 2 0 , j were studied in O.lm to 25m NaOH solutions at 150°C to 200"C, where m = mol/(kg of H20j. The attack of the caustic alkaline solution started at the grain boundaries. Consequently, the corrosion resistance increased with decreasing SiO, content in Al2O3 ceramics, and the corrosion resistance of 99.5% pure A1203 was similar to that of Si3N4 ceramics. Since large pits are formed by cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 6 publications
2
47
0
Order By: Relevance
“…Studies of the corrosion resistance of Si 3 N 4 materials revealed a strong relationship between the stability of the grain boundary and the corrosion resistance of the ceramic material (Galuskova et al, 2011b;Herrmann & Schilm, 2009;Herrmann et al, 2006;Herrmann, 2005;Herrmann, 2012;Kitaoka et al, 1994;Kleebe et al, 1993;Nagae, Koyama, et al, 2006;Sato Figure 14 Potential effect of corrosion on the integrity of zirconia components (after Chevalier et al, 2009Chevalier et al, ). et al, 1988aChevalier et al, , 1988bSato et al, 1992;Schilm et al, 2003;Schilm et al, 2004a;Schilm et al, 2006;Schilm et al, 2007;Schilm, 2004;Seipel & Nickel, 2003;Shimada & Sato, 1989;Somiya, 2001).…”
Section: Corrosion Of Different Ceramics In Aqueous Solutionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies of the corrosion resistance of Si 3 N 4 materials revealed a strong relationship between the stability of the grain boundary and the corrosion resistance of the ceramic material (Galuskova et al, 2011b;Herrmann & Schilm, 2009;Herrmann et al, 2006;Herrmann, 2005;Herrmann, 2012;Kitaoka et al, 1994;Kleebe et al, 1993;Nagae, Koyama, et al, 2006;Sato Figure 14 Potential effect of corrosion on the integrity of zirconia components (after Chevalier et al, 2009Chevalier et al, ). et al, 1988aChevalier et al, , 1988bSato et al, 1992;Schilm et al, 2003;Schilm et al, 2004a;Schilm et al, 2006;Schilm et al, 2007;Schilm, 2004;Seipel & Nickel, 2003;Shimada & Sato, 1989;Somiya, 2001).…”
Section: Corrosion Of Different Ceramics In Aqueous Solutionsmentioning
confidence: 96%
“…Even in supercritical water, they exhibit a high-corrosion resistance (Franks & Gan, 2007;Galuskova et al, 2011a;Genthe & Hausner, 1989;Genthe & Hausner, 1992;Hirata et al, 2003;Hoppert, 2010;Kitaoka et al, 1992;Mikeska et al, 2000;Mikeska, 1999;Oda & Yoshio, 1997;Sato et al, 1991). Silica and alkaline additives in alumina often used to reduce the sintering temperature are leached out in acids and under hydrothermal conditions (Figures 9 and 13).…”
Section: Corrosion Of Different Ceramics In Aqueous Solutionsmentioning
confidence: 96%
See 1 more Smart Citation
“…5,7,8 The proposed mechanism of the formation of a stable hydrated SiO 2 -rich network is also in agreement with the different corrosion behaviour of Si 3 N 4 ceramics in HF and under hydrothermal conditions. 4,11,15,[24][25][26][27] The process of formation of a stable passivating SiO 2 network in the ceramics is strongly accelerated by an increasing concentration of SiO 2 in the grain boundary of the ceramics (Fig. 13).…”
Section: Dissolution Of the Grain Boundary Phase And Formation Of Promentioning
confidence: 99%
“…Linear corrosion kinetics are generally explained by the interfacial controlled dissolution of the grain boundary phase. [24][25][26][27] The corrosion rate can be explained based on the stability of the oxynitride glassy grain boundary phase and can be directly related to the corrosion rate of the oxynitride glasses with the same composition as the grain boundary (see part 1). 1 For high corrosion depth and geometries like balls or bending bars the shrinking core effect has to be taken into account.…”
Section: Corrosion Kineticsmentioning
confidence: 99%